Study of homogenization on media milling time in preparation of irbesartan nanosuspension and optimization using design of experiments (DoE) - Chetan Borkhataria; Dhavalkumar Patel; Swati Bhagora; Nilesh Patel; Kalpesh Patel; Ravi Manek (SpringerOpen, 2020)
Abstract Background The present investigation aimed at preparing nanosuspension of irbesartan to improve its dissolution. Dissolution enhancement of irbesartan can improve the oral bioavailability. Here, it was also studied how media milling time can be reduced by subjecting irbesartan to prior homogenization and then media milling. Results First, homogenization of irbesartan was carried out in the presence of poloxamer 407 at 6000 rpm for 2 h. Final nanosuspension preparation was done by media milling with zirconium dioxide beads. Here, the amount of poloxamer 407 and zirconium dioxide beads was studied as statistical independent variables. Response surface plot analysis and desirability function were applied to the selected optimized batch. The prepared batches were subjected to evaluation for zeta potential value, mean particle size, PDI, dissolution study, and stability study. Target particle size was less than 500 nm, and in vitro dissolution in 10 min was more than 80%. Zeta potential value was ~ 27 mV for optimized nanosuspension. Desirability of 0.941 was achieved. Checkpoint batch was prepared and evaluated to confirm the validity of mathematical model. Accelerated stability study was performed on the optimized batch at 40 ± 2 °C/75 ± 5% RH for 6 months. Conclusion The results confirmed the stability of formulation at accelerated stability conditions. Using presuspension prepared by homogenization, media milling time primarily reduced from 24-28 h to 18 h. Future perspective is to study other factors in combination method in discrete.